The Effect of Climate Elements Represented by Temperature, Wind Speed, Relative Humidity and Precipitation on the Production of Organic Barley Harvest in the Kingdom of Bahrain - Galadari, Huda Fadhalalla (Journal of agricultural, environmental and veterinary sciences, 2024)
The present research aimed to investigate the effect of climate elements represented by temperature, wind speed, relative humidity, and precipitation on the production of organic barley crops in the Kingdom of Bahrain. This research was prepared during the agricultural season 2023-2024 on a plot of land measuring 24 square meters in Hamad Town, Kingdom of Bahrain. Organic barley grains of the Rayhan variety were used. The researcher used Bahrain Weather Climate Reports from The Bahrain Meteorological Directorate and used the statistical processing (SPSS Statistics) to find the Pearson Correlation Coefficient between the elements, and data tables to calculate percentages and means. The results showed that the research hypothesis was achieved, and an abundant barley crop was obtained, amounting to approximately 600%. The research reached some proposed recommendations, such as encouraging investment in the agricultural sector to increase the area of land planted with grain crops, specifically barley, and enhancing farmers' trends to expand barley cultivation, in addition to urging individuals to contribute to expanding the green area and working to combine efforts to maintain a sustainable environment.
Keywords: Climate elements; Barley crop; Field crops; Kingdom of Bahrain